Automatic Footstep Design and The use of LDR Sensors in Vehicles - Ian Hardianto Siahaan (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2022)
Vehicle modification has become a necessity for its users; this is done to get a practical and modern impression and consider the functionality side. One of the modified parts of the vehicle is the footstep feature. This component is beneficial as a support point when getting in and out of the car. Initially, the presence of this component was found in many SUVs, and this is because these types of vehicles generally have high ground clearance, making it difficult for vehicle owners to get into the car. The step function finally changed to make the car look more elegant from the left and right sides. Footstep designs that are common in the market are permanent. When installed in the vehicle, its position protrudes from the car body. Footstep will add to the dimension of the car and is quite annoying when the car crosses a narrow road. Therefore, a footstep mechanism was designed to enter the car body when the door is closed and go down and protrude when the car door is opened. The LDR sensor, which adjusted the LED lights, is applied to ensure adequate lighting for the passengers to see the footsteps in the dark conditions. So, the lighting leads to the footstep board and the side of the c ar when the door is opened. From the tests carried out, the longest time to open the footstep is 0,84 seconds, and the longest time to close the footstep is 1,09 seconds. These results indicate that the target time has been met, which does not exceed 1,5 seconds with or without load on the experiment.